Aggressiveness and trichothecene production of Fusarium graminearum isolates from cereals in Serbia - Obradović, Ana; Vukadinović, Jelena; Nikolić, Milica; Bulajić, Aleksandra; Stanković, Goran; Delić, Nenad; Stanković, Slavica (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
The aim of this study was to assess variations in aggressiveness and trichothecene production of F. graminearum isolates originating from maize, wheat and barley in Serbia. Analyzing F. graminearum isolates (98) obtained from various agroecological conditions of Serbia over the period from 1993 to 2010, using the HPLC method, the following two chemotypes were observed: 3-acetyl-deoxinivalenol (3ADON) and 15-acetyl-deoxinivalenol (15ADON). A great diversity in the production of deoxinivalenol (DON) derivatives was observed. A majority of F. graminearum isolates, regardless of their origin (maize, wheat or barley) belonged to the 15ADON chemotype. The 3ADON chemotype was also detected, but in a significantly smaller number (13/98) samples, compared to the 15ADON chemotype (85/98). None of the tested isolates belonged to the NIV chemotype. The examined isolates showed different pathogenicity on barley leaf, wheat class and maize ears. The average pathogenicity of the tested isolates was the highest on barley leaf. It was observed that isolates originating from wheat had the highest average daily increase in mycelium growth rate (27.37 mm). Statistical analysis of the obtained results for mycotoxins synthesis showed that there was a highly significant statistical correlation between the production potentials of total DON, 3ADON and 15ADON in F. graminearum isolates belonging to various chemotypes. However, there was no statistically significant correlation between the aggressiveness of isolates and the production of total DON in isolates belonging to 3ADON and 15ADON chemotypes.
Keywords: cereals, Fusarium graminearum, mycotoxins, chemotypes, trichotecene, pathogenicity